Turning characteristics of biomimetic robotic fish driven by two degrees of freedom of pectoral fins and flexible body/caudal fin. (2nd January 2018) - Li, Zonggang; Ge, Liming; Xu, Weiqiang; Du, Yajiang
This article considers the turning characteristics of robotic fish with two-degree-of-freedom pectoral fins and flexible body/caudal fin. The hydrodynamics are first established for three cases propelled by both sides of pectoral fins, flexible body/caudal fin, and composite of them. Then, the turning characteristics of such three cases are analyzed by numerical simulations and experiments. The results show that if robotic fish is cooperatively propelled by pectoral fins and flexible body, it can obtain the fast turning speed and the average turning speed is up to 0.6 rad s −1 . The smallest turning speed is achieved as robotic fish is only propelled by pectoral fins; however, it can turn on the spot in this case. The presented results provide the more abundant ways of turning, the better maneuverability, and the higher turning speed for the proposed robotic fish.